The foreclosure echo how the hardest hit have been left out of the economic recovery - Fisher, Linda E. 1953-; Fox, Judith L. (Cambridge University Press, 2019)
The Foreclosure Echo tells the story of the ordinary people whose quest for the American dream was crushed in the foreclosure crisis when they were threatened with losing their homes. The authors, Linda E. Fisher and Judith Fox - each with decades of experience defending low-to-moderate-income people from foreclosure and predatory lending practices - have employed a range of legal, economic, and social-science research to document these stories, showing not only how people experienced the crisis, but also how lenders and public institutions failed to protect them. The book also describes the ongoing effects of the crisis - including vacant land and abandoned buildings - and how these conditions have exacerbated the economic plight of millions of people who lost their homes and have increased inequality across the country. This book should be read by anyone who wants to understand the fallout of the last financial crisis and learn what we can do now to avoid another one
Title from publisher's bibliographic system (viewed on 15 Jul 2019)
The housing crisis -- The breakdown of mortgage servicing & loss mitigation -- Zombie mortgages & abandoned properties -- The benefits & harms of intervention -- Rethinking home : housing post-crisis -- Foreclosure or a more sustainable mortgage? -- Picking up the pieces & revitalizing neighborhoods -- Where do we go from here?
Keywords: Foreclosure / Economic aspects / United States